On the intersection of weighted Hardy spaces - Dilnyi, V.M.; Hishchak, T.I. (Carpathian Mathematical Publications, 2016)
Let H^p_σ( C_+), 1≤ p <+∞, 0≤ σ < +∞, be the space of all functions f analytic in the half plane C_+= { z: Re z>0 } and such that \|f\|:=_φ(-π2;π2){_0^+∞ |f(re^iφ)|^pe^-pσ r|φ|dr}^1/p<+∞. We obtain some properties and description of zeros for functions from the space _σ>0 H^p_σ(C_+).